Yield and Nutritional Status of Cucumis sativus under Different Growing Conditions in the Pacific Coast of Ecuador. Issue 17 (25th September 2018) - Salcedo, Galo Alberto; García-Caparrós, Pedro; Reca, Juan; Pérez-Saiz, Mónica; Lao, María Teresa
ABSTRACT: The growth of cucumber under open field conditions in the coast of Ecuador results in low yields being the growth under protected conditions a tentative solution, but there is little information about the nutritional status of this crop in this region. The objectives were to determine the yield, nutritional status as well as the water and nutrient use efficiencies. The different growing conditions were: multitunnel greenhouse with soilless system (GSL), multitunnel greenhouse with soil system (GS) and open field conditions with soil system (OFS). Cucumber plants grown under GSL had the highest yield. The nutrient concentration in leaf showed different trends: nitrogen (N), calcium (Ca) and iron (Fe) remained unchanged. Phosphorus (P), potassium (K), magnesium (Mg), copper (Cu), zinc (Zn) and manganese (Mn) showed variations according to the growing conditions and phenological stages. The highest values of water and nutrient use efficiencies under GSL were related to the highest yield.